2017
DOI: 10.1532/hsf.1736
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Neutrophil to Lymphocyte Ratio and Risk Factors for Mortality in Patients with Stanford Type A Aortic Dissection

Abstract: Background: Neutrophil to lymphocyte ratio (NLR) is a prognostic predictor in a wide range of cardiovascular disease. Acute aortic dissection (AD) is an uncommon but fatal cardiovascular disease. In this study, we investigated both prognostic factors in patients with AD and whether NLR can be a predictor for mortality. Methods: We analyzed retrospectively the data of 57 patients with AD who had undergone emergent surgery in our hospital and included 128 consecutive patients with chest pain admitted to the emer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…Previous studies have demonstrated the neutrophil/lymphocyte ratio (NLR) to be a good predictor of inhospital mortality [6,11,29]. In Karakoyun et al's study [11], they found that an NLR >8.51 yielded an AUC value of 0.829.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the neutrophil/lymphocyte ratio (NLR) to be a good predictor of inhospital mortality [6,11,29]. In Karakoyun et al's study [11], they found that an NLR >8.51 yielded an AUC value of 0.829.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with ATAAD, hemodynamic instability can occur as a result of cardiac tamponade or aortic insufficiency, and emergency aortic repair under cardiopulmonary bypass induces a strong perioperative inflammatory response, making investigation of the early inflammatory response more complicated. Nevertheless, there is evidence that systemic inflammation characterized by elevation of the white blood cell (WBC) count [12][13][14] or an increased neutrophil/lymphocyte ratio [13,15,16] influences outcomes in patients with ATAAD. Although biomarkers of disordered coagulation and fibrinolysis D-dimer and fibrin degradation products have been well studied in relation to acute aortic dissection [17][18][19], WBC count elevation and its etiology in cases of acute aortic dissection have not been fully elucidated, and the relation between WBC elevation and dissection morphology is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A study of patients who had Stanford A type acute aortic dissection claimed that increased NLR is useful to predict short-term mortality along with other parameters (16). In a study evaluating patients with endocarditis, it was shown that increased NLR alone directly affects the symptoms of endocarditis and is a good predictor of prognosis (17).…”
Section: Discussionmentioning
confidence: 99%